Assessing Thermic Degradation for Yttrium–aluminum Precursive Agents Applied to YAG Phosphor Samples - Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh; Phan Thi Minh Man; Hsiao-Yi Lee (Science and Technology Indonesia, 2025)
Several forms of precursive agents were made via the soggy chemical approach, beginning with yttrium–europium–aluminum nitrate (YEAN) compoundaswell as disparate precipitants, comprising urea, oxalic acid, as well as ammonium carbonate. The precursive agents were heat-treated within nitrogen aerosphere for acquiring Y3Al5O12:Eu3+ featuring garnet formation YAG:Eu. Procedures employed for thermic degradation as well as constitution for precursive agents were validated via thermic assessment as well as FTIR spectroscopic assessment. Relationship among thermic degradation stages, as well as gaseous constitution developed throughout thermic procedure was identified via the merger between thermic assessment as well as FTIR. Ultimately, the disparate constitution for precursive agents signifies the luminescent attributes for matching phosphor samples. Urea as well as ammonium carbonate generate YAG samples featuring garnet formation as well as certain red discharge. Regarding oxalic acid, the precipitant yields an ununiform sample featuring yttrium oxide in the form non-pure stage. Said sample would be a merger between Y2O3:Eu3+,Y4Al2O9:Eu3+, as well as Y3Al5O12:Eu3+, yielding greater discharge intenseness. When used in tandem with YAEN, AlAs was investigated for its particle size’s effect on optical properties, such as scattering coefficient, YAG:Ce concentration, correlated color temperature (CCT), chroma aberration, lumen, and color rendition. It was found out 19 wt.% would be the most optimal particle size when all of these properties are taken into account.